Electromechanical Dyssynchrony and Resynchronization of the Failing Heart - Kirk, Jonathan A. (2013)
Patients with heart failure and depressed function frequently develop discoordinate contraction due to electrical activation delay. Often termed dyssynchrony, this further depresses systolic function and chamber efficiency, and worsens morbidity and mortality. In the mid-1990s, a pacemaker-based treatment termed cardiac resynchronization therapy (CRT) was developed to restore mechanical synchrony by electrically activating both right and left sides of the heart. It is a major therapeutic advance for the new millennium.. Acute chamber-effects of CRT include increased cardiac output and mechanical efficiency, and reduced mitral regurgitation, while reduction in chamber volumes ensues more chronically. Patient candidates for CRT have a prolonged QRS duration and discoordinate wall-motion, although other factors may also be important as ∼30% of such selected subjects fail to respond to the treatment. In contrast to existing pharmacological inotropes, CRT both acutely and chronically increases cardiac systolic function and work yet it also reduces long-term mortality. Recent studies reveal unique molecular/cellular changes from CRT that may also contribute to this success. Heart failure with dyssynchrony displays depressed myocyte and myofilament function, calcium handling, beta-adrenergic responsiveness, mitochondrial ATP-synthase activity, cell survival signaling, and other changes. CRT reverses many of these abnormalities often by triggering entirely new pathways. In this review, we discuss chamber, circulatory, and basic myocardial effects of dyssynchrony and CRT in the failing heart, and highlight new research aiming to better target and implement CRT as well as leverage its molecular effects.